Ultrafast Activating Strategy to Significantly Enhance the Electrocatalysis of Commercial Carbon Cloth for Oxygen Evolution Reaction and Overall Water Splitting. Issue 4 (25th February 2020) - Huang, Kun; Hu, Aiping; Huang, Cong; Li, Yanhua; Zhou, Haifeng; Xu, Yali; Tang, Qunli; Zhou, Shengping; Chen, Chuansheng; Chen, Xiaohua
Abstract: It is of desirability to prepare in situ self‐supporting electrocatalysts not only to meet application requirements but also to simplify the production process of working electrodes. In this work, oxygen‐containing free‐standing carbon cloth with abundant pores (e‐CC−H2 ) has been obtained through a facile two‐step electrochemical oxidation and hydrogen etching method. Compared to the previous activation strategies of carbon cloth (such as chemical activation), this method has the advantages of simplicity, time‐saving, low‐cost and energy‐saving. Benefiting from the abundance of defects and oxygen‐containing functional groups that are active sites for oxygen evolution reaction, the obtained e‐CC−H2 shows excellent electrocatalytic activity, with a low overpotential of 350 mV at a current density of 10 mA cm −2, a low Tafel slope (127 mV dec −1 ) and stable electrochemical activity. This strategy paves the way for the application of functionalized and flexible materials in the field of electrochemical energy storage. Abstract : Through an ultrafast two‐step strategy, defects‐ and oxygen‐rich carbon cloth electrocatalysts with a porous surface were obtained. The activated carbon cloth‐based electrocatalysts exhibit an excellent electrocatalytic performance and electrochemical kinetics. Moreover, this strategy with low‐cost and time‐saving paves the way for the application of functionalized and flexible materials in the field of electrochemical energy storage.